AFIKSASI BAHASA MELAYU DIALEK NGABANG - simanungkalit, Rinni Juliati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractBMDN (Malay dialect Ngabang language) has grown and developed at Ngabang regency Landak. The limitation of the problem divided in to three sub problem, there are form, function, meaning. BMDN affixation is described by descriptive method from survey method, observation, and interview, qualitative type. The data source is native speaker BMDN. The technique used in accumulation the data is observation, conversation, writing, and recording technique. The instrument of this research is tape recorder, images, legends, identification cards, and stationary as well as researchers as the main instrument. Technique of analysis the data is transcribe the data and then translate in to Indonesia after that classified by the problem of the research. Based on the analysis the data, result of the research showed Affix in BMDN has form, function, meaning. There are prefix, suffix, confix. There are 8 The prefix form. there are 5 the suffix form. There are 6 confix form. Functions of affix in BMDN are intransitive verb, passive verb, nouns, adverbs, numeral, active verb, transitive verb. The meaning of the afffix is a active deeds, use or wear, do the deeds, get or produce, has or have, suddenly, one, a passive deeds, collections, tools, job to do deeds, use, do order, proportion, possession, do something, management or position, place and show time, protect, prepare, transfer.Â Keywords: Affixation, form affix, function affix, meaning affix, BMDN